Hippocrepis fuelleborni (Digenea: Notocotylidae) from Argentina, morphological, molecular and phylogenetic studies - Martins, Natalia Beatriz Guerreiro; Robles, María Del Rosario; Canova, Victoria; Diaz, Julia Inés; Balcazar, Dario; Callejón, Rocío (Zootaxa, 2024)
Notocotylidae is a family with a cosmopolitan distribution, with 13 genera parasitizing birds and mammals. Four of these genera were registered in the Americas, and two parasitizing rodents in Argentina. In this paper, specimens of the genus Hippocrepis parasitizing Holochilus brasiliensis from Argentina are studied on the basis of morphological and molecular characteristics. Eleven Ho. brasiliensis specimens were collected in seven localities from the Cuenca del Plata region. A total of 192 specimens of digeneans were found in a single Ho. brasiliensis. Conventional morphological and molecular analyses were used. The digenean specimens were identified as Hippocrepis fuelleborni. Furthermore, the molecular characterization of three genetic markers for Hi. fuelleborni is provided. This study contributes to the first record of the genus Hippocrepis in cricetid rodents. The continuity of the studies on this genus and the incorporation of more haplotypes from different genera of Notocotylidae will allow us to recognize the relationship among genera and provide a new systematic proposal.